Dissipation kinetics of organophosphorus pesticides in milled toasted maize and wheat flour (gofio) during storage. (15th August 2017) - González-Curbelo, Miguel Ángel; Socas-Rodríguez, Bárbara; Herrero, Miguel; Herrera-Herrera, Antonio V.; Hernández-Borges, Javier
Highlights: A modified QuEChERS method was validated and applied for sample analysis. After 90 days of storage, residues of all pesticides were found in both matrices. Dissipation curves fitted to a first-order decay curve. Dissipation of organophosphorus pesticides was slower in milled toasted maize gofio than in milled toasted wheat gofio. None of the selected metabolites were detected in any of the samples. Abstract: The dissipation/degradation of the pesticides dimethoate, terbufos, disulfoton, and pirimiphos-methyl were evaluated in milled toasted maize and wheat flour (gofio) during three months of storage. Their dissipation kinetics and residual levels were determined, as well as their possible decomposition into some of their main transformation products (disulfoton sulfoxide, terbufos sulfone and disulfoton sulfone). For this purpose, pesticide-free milled toasted maize and wheat samples were spiked with the pesticides, and they were then stored in the darkness at ambient temperature in a closed container to simulate current storage conditions of such packed food. A multiresidue analysis based on the QuEChERS ( Quick, Easy, Cheap, Effective, Rugged and Safe ) method was performed for the simultaneous determination of these pesticides and their metabolites. After three months of storage, the dissipation of residues ranged between 34% (pirimiphos-methyl) and 86% (disulfoton) for maize gofio and between 69% (terbufos) and 92% (disulfoton and pirimiphos-methyl) for wheat gofio. The results demonstrated that the degradation was slower in gofio than in wheat gofio and that none of the selected metabolites were detected in any of the samples. Dissipation curves of all studied pesticides fitted to a first-order decay curve in both types of cereals.